2018
DOI: 10.1016/j.seppur.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale ELAN ® process applied to treat primary settled urban wastewater at low temperature via partial nitritation-anammox processes

Abstract: A single stage partial nitritation and anammox granular pilot scale reactor (600 L) was operated to treat primary settled sewage in an urban wastewater treatment plant. The fed wastewater contained low total nitrogen concentrations of 6-25 mg TN/L and the system operated without temperature control ranging from 18 to 12 ºC. A control strategy, based on the pH value, was applied to stop the aeration supply. The pH setpoint was fixed at 6.0 and allowed obtaining a total nitrogen removal efficiency approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 33 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The low effluent quality was already pointed out as one of the drawbacks of the continuously fed PN/AMX systems by Hoekstra et al (2018) who operated a 4-m 3 complete mixed reactor where NRR as high as 97 g N/(m 3 •d) at 13.4 ± 1.1 °C were reached. In this sense, the plug flow reactors (Lotti et al, 2015;Yang et al, 2017) or SBRs (Laureni et al, 2016;Pedrouso et al, 2018) are presumably more suitable for effluent quality optimization than the continuous complete mixed ones. Actually, it was demonstrated that using a residual ammonium concentration (2 -5 mg N/L) as set point either to terminate the reaction (Laureni et al, 2016) or to adjust the airflow rate (Yang et al, 2017) or the HRT (Malovanyy et al, 2015), higher NRE are achieved.…”
Section: Removal Rate and Effluent Quality Of The Pn/amx Systems At Mainstream Conditionsmentioning
confidence: 99%
“…The low effluent quality was already pointed out as one of the drawbacks of the continuously fed PN/AMX systems by Hoekstra et al (2018) who operated a 4-m 3 complete mixed reactor where NRR as high as 97 g N/(m 3 •d) at 13.4 ± 1.1 °C were reached. In this sense, the plug flow reactors (Lotti et al, 2015;Yang et al, 2017) or SBRs (Laureni et al, 2016;Pedrouso et al, 2018) are presumably more suitable for effluent quality optimization than the continuous complete mixed ones. Actually, it was demonstrated that using a residual ammonium concentration (2 -5 mg N/L) as set point either to terminate the reaction (Laureni et al, 2016) or to adjust the airflow rate (Yang et al, 2017) or the HRT (Malovanyy et al, 2015), higher NRE are achieved.…”
Section: Removal Rate and Effluent Quality Of The Pn/amx Systems At Mainstream Conditionsmentioning
confidence: 99%
“…[1][2][3] However, its independent use is limited since it requires nitrite nitrogen as an electron acceptor. At present, partial nitrication is the main route to obtain NO 2 À -N; however, it has high control requirements, is easily destroyed, 4,5 and is difficult to recover once destroyed. Therefore, new approaches are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Those reactors type must have allowed keeping higher N-NH 4 bulk concentrations over the substantial period of time (after starting aeration cycle in SBR). As explained above, the positive effect of such conditions on nitrogen removal rate by AOB was possibly reinforced by high residual N-NH 4 [17,18,25,28,30,34,39]. There are proofs that biomass growing in the PN/A systems can be enriched with AOB by the application of high nitrogen loading rate [25].…”
Section: Comparison With Results From Empirical Studiesmentioning
confidence: 93%
“…Although the studies of Regmi et al [6,7] and Al-Omari et al [8] explained the logic of application of an aeration strategy with a relatively high dissolved oxygen concentration (above 1 mgO 2 /l) and intermittent aeration, in the available literature there is no explicit proof that a specific range of dissolved oxygen concentration (DO) and intermittent aeration leads to efficient mainstream PN/A process (Figure 1(B) 'MBBR') [4,5,31,[38][39][40]. That strategy had a desired effect only when AOB bacteria were kept in the system, in the form of activated sludge, by recirculating a detached biofilm from the secondary clarifier to bioreactor or inoculation of the MBBR bioreactor with the activated sludge originated from a conventional SBR for municipal wastewater treatment (transition of the bioreactor operation from MBBR to IFAS mode) [4,5].…”
Section: Introductionmentioning
confidence: 99%